PENINGKATAN KETERAMPILAN SOSIAL DAN KERJASAMA PESERTA DIDIK MELALUI KEGIATAN METAPRO KELOMPOK B4 TK ‘AISYIYAH BUSTANUL ATHFAL 7 KOTA MADIUN - Eko Wahyuni, Dwi; Sudarmiani; Nugraha, Nurhadji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ social skills and collaboration through metapro activities in Group B4 of TK ‘Aisyiyah Bustanul Athfal 7 Kota Madiun during the 2024/2025 academic year. The research employed Classroom Action Research (CAR) conducted in two cycles, involving 14 students with developing social skills (MB) out of 17, and 15 students with developing collaboration skills (MB) out of 17. The research followed the stages of planning, implementation, observation, and reflection. Data were collected through observation, interviews, and documentation, and analyzed descriptively using quantitative percentages of mastery.The results showed an improvement in students’ social skills, including communication, empathy, and sociability, as well as enhanced collaboration skills such as sharing with peers, helping within groups, and active participation in group activities. Thus, metapro activities proved effective in improving the social skills and collaboration of Group B4 students at TK ‘Aisyiyah Bustanul Athfal 7 Kota Madiun.